Gaon : Conflict and Cohesion in an Indian Village - Orenstein, Henry (Princeton Legacy Library, 2016)
This study opposes the prevailing view that Indian villages have little social solidarity and points out the relationship between village solidarity and the potentially centrifugal factors of caste, conflict, and power. Originally published in 1965. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.